2004
DOI: 10.2320/matertrans.45.376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nanocrystalline Surface Layer in Steels Formed by Air Blast and Ultrasonic Shot Peening

Abstract: Surface nanocrystallization in various steels by shot peening (both air blast (ABSP) and ultrasonic (USSP)) was investigated. In all the shot-peened specimens, the equiaxed nanocrystals with grain size of several 10 nm were observed at the surface regions. The depth of nanocrystalline (NC) layers was several mm. The NC layers have extremely high hardness and were separated from the deformed structure regions just under the NC layers with sharp boundaries. By annealing, the NC layers show the substantially slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…The most common and well studied gradient structure is grain size gradient structure [1][2][3][4][5], which often consist of nanocrystalline or ultrafine grains at the surface of a tensile sample, which gradually transition to coarse grains in the interior over distances of~50 μm or longer. Although the means by which gradient microstructures can be created include Surface Mechanical Grinding Treatment, Surface Mechanical Attrition Treatment (SMAT), Ultrasonic Shot Peening [11], Wire Brushing [12], and Air Blast Shot Peening [13], most of the seminal work was undertaken with SMAT [1,10,12,[14][15][16]. Much like conventional shot peening, SMAT uses round balls to repeatedly impact the surface of a material.…”
mentioning
confidence: 99%
“…The most common and well studied gradient structure is grain size gradient structure [1][2][3][4][5], which often consist of nanocrystalline or ultrafine grains at the surface of a tensile sample, which gradually transition to coarse grains in the interior over distances of~50 μm or longer. Although the means by which gradient microstructures can be created include Surface Mechanical Grinding Treatment, Surface Mechanical Attrition Treatment (SMAT), Ultrasonic Shot Peening [11], Wire Brushing [12], and Air Blast Shot Peening [13], most of the seminal work was undertaken with SMAT [1,10,12,[14][15][16]. Much like conventional shot peening, SMAT uses round balls to repeatedly impact the surface of a material.…”
mentioning
confidence: 99%
“…In this work, USP can refine the surface grains of pure Ti into the nanoscale range (Figure 3), which is agreement with previous studies. 17,19,20 When inserted in cortico-cancellous bone in an in vivo rabbit femur implantation model, USP-Ti demonstrated superior osseointegration to that seen for Ti, with firm abutments between the surface of material and the surrounding bone tissue. Histological analysis showed that new bone was formed and filled up the gap between the implants and bone for USP-Ti in direct contact with the implant, compared with that for Ti.…”
Section: Discussionmentioning
confidence: 99%
“…Surface severe plastic deformation (S 2 PD), as a representative technique, can fabricate effectively surface nano-crystallized graded materials, which consist of a graded layer (GL) with grain size varying from tens of nanometers to a few micrometers and a coarse grained (CG) substrate with grain size in tens of micrometers, such as copper [2], Al-alloy [3], Fe [4] and stainless steel [5,6]. Due to different fabricating methods [7], S 2 PD includes shot peening (SP) [8][9][10], air blast shot peening (ABSP) [11][12][13], sandblasting (SB) [14][15][16], surface nanocrystallization and hardening (SNH) [17][18][19][20], surface mechanical attrition treatment (SMAT) [1,5,21], particle impact processing (PIP) [11], etc. The fundamental procedure of S 2 PD is to impact repeatedly the surface of CG materials with balls.…”
Section: Introductionmentioning
confidence: 99%